Coronavirus disease-19 and diabetes mellitus: implications for diabetes management in Nigeria - Agofure, Otovwe; Eduviere, Anthony Taghogho; Okandeji-Barry, Oghenenioborue Rume (International Journal Of Community Medicine And Public Health, 2021)
Coronavirus disease-19 is a viral infection that has spread to the entire regions across the globe. Current evidence shows that diabetes mellitus patients are highly susceptible to severe complications, morbidity and mortality due to this infection. The high susceptibility may be as a result of the associated pathophysiology of coronavirus disease-19 and diabetes mellitus co-morbidity in affected individuals. This narrative review was undertaken to highlight the implications of coronavirus disease-19 infection on diabetes mellitus patients in developing countries with a focus on Nigeria which has a weak health care system and poor clinical patients’ characteristics. A critical literature search was carried out on coronavirus disease-19 and diabetes mellitus. Relevant items were assembled to form the current review on coronavirus disease-19 infections and its implications on diabetes mellitus management in developing countries. The review highlighted the significance of proper glycaemic control as coronavirus disease-19 increases the susceptibility of diabetes mellitus patients to morbidity and mortality which could be overwhelming as the incidence of the infection increases across developing countries like Nigeria.